Talent Development through Familial Environment - Senad BECIROVIC; Azamat AKBAROV (Association of Social and Educational Innovation, 2016)
This article presents some of the main results from the research about development of talented students in mathematics. The research is focused on identification, analysis, and interpretation of all or most factors in the family environment that contribute to development of mathematical talent. The research results reveal the specific methods, actions, strategies, and other variables of the home environment that influence and affect development of mathematical talent. The revealed principles involved in the educational development of talented students will allow parents and educators to improve, modify, and develop new strategies of dealing with talented students in an attempt to enhance their outstanding development. This research is very important from scientific, social, and practical aspects. Parents, teachers, administration, policy makers, and the entire society have to support identification and development of talented students because of their remarkable contribution to science, culture, technology, and welfare of the society in general.